Synthesis and Electroluminescence Properties of New Blue Emitting Polymer Based on Dual-Core Type for Solution Process OLEDs - Kang, Seokwoo; Kwon, Hyukmin; Jeong, Jinwook; Kim, Young-Chul; Park, Jongwook (Macromolecular research, 2022)
Based on the anthracene-pyrene dual core, a new blue fluorescent material in the form of a polymer was developed. After introducing styrene at the end of the dual-core, a polymer blue emitting material was obtained through radical polymerization. In the case of the newly synthesized Poly 1-(4-vinylphenyl)-6-(10-(4-vinyl-phenyl)anthracen-9-yl)pyrene (S-AP-S), it not only emitted in the blue region of 443 nm in solution state, but also showed a high photoluminescence quantum yield (PLQY) of 79%. When Poly S-AP-S was applied as an emitter to solution process organic light-emitting diodes (OLEDs), current efficiency of 4.48 cd/A and external quantum efficiency (EQE) of 3.62% were realized. It also exhibited the deep-blue color coordinates of (0.157, 0.094) which satisfy with the mobile specification.